Researching life stories and family histories - Miller, Robert L. (Robert Lee), 1948- (London : SAGE, 2000)
Researching Life Stories and Family Histories is a concise guide to the methods and issues involved in carrying out biographical life history or family history research.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Genealogy; Biography -- Research -- Methodology; Biography as a literary form; Interviewing